Value orientations toward wild meat in Guyana are determined by gender, ethnicity, and location - Paemelaere, Evi A.D.; Puran, Anupana; Williams, Timothy; Agard, Gavin; Pierre, Mia A.; Yang, Huichang; Kenyon, Ayla; Zammett, Jose; van Vliet, Nathalie (Frontiers in Conservation Science, 2024)
Understanding what drives differences in values towards wild meat is important for developing legislation and behavioral change campaigns that promote sustainable use. Value orientations (VOs) underly behavior. VOs are influenced by personal (e.g., gender, generation), social (e.g., media, family), location (e.g., rural versus urban) and experience determinants. In Guyana, an ethnic diverse nation in South America, the national hunting laws have recently been instated. The wildlife management agency is rolling out a behavioral change campaign in collaboration with a sustainable use initiative. To support this campaign, we evaluated VOs towards wild meat across Guyana. Applying Multiple Correspondence Analysis and generalized linear models to data from interviews, we examined location, personal, and societal determinants for their influence on these VOs, and explored how VOs translated into behavior, specifically wild meat consumption frequency. Location (Indigenous, and coastal: rural, town, urban), intertwined with ethnicity, and gender showed the strongest associations with variation in VOs. Respondents from Indigenous territories expressed mostly positive VOs compared to coastal Guyanese. Women expressed more neutral or negative, and more negative biocentric VOs compared to men, and this difference was largest among Indigenous but non-existent in urban sites. Negative anthropocentric VOs towards wild meat consistently grouped together and dominated amongst those not consuming wild meat. Highest consumption was seen among those expressing positive materialistic VOs. Positive anthropocentric VOs were associate with intermediate consumption frequencies and most typical for men. Those expressing negative values towards wildmeat based on biocentric orientations towards wildlife consumed wild meat, but rarely. Our results direct behavioral change efforts to men on the coast who consume wild meat for enjoyment at bars, restaurants or family events. Based on our study, positive messaging promoting the coexistence between consumption of mostly resilient species and caring about wildlife would be well-received to support sustainable use policies.